It's getting tight in the Alps - challenges and implications of the e-mountain bike boom for sustainable tourism management. (24th February 2022) - Moesch, Christian; Christen, Samuel; Ströbel, Tim
This study analyses the challenges and implications of technological development in mountain-bike sports for Alpine tourism destinations. We investigate the motivations of e-mountain bikers in tourism destinations and derive implications for tourism managers to handle dynamic technological developments in a sustainable manner. A mixed-method design including qualitative in-depth interviews with relevant actors and a quantitative survey with 175 e-mountain bikers was applied. The e-bike boom offers potential and challenges for sustainable tourism management in Alpine destinations. Tourism managers must develop diverse, participatory, and nature-friendly concepts as well as collaborations with nearby destinations and recreational areas to control the flow of tourists within ecologically sensitive areas.